ANALISA KEGAGALAN INTI CETAKAN JENIS SKD 61 PADA PROSES PELEBURUAN DENGAN CARA DIECASTING - Irawan, Surya; Hermanto, Bambang (JURNAL ILMIAH TEKNIK SIPIL, 2023)
Damage to the surface of the mold core by loss of the nitride layer from the surface hardening process, namely the name of the surface hardening process for the mold core, namely Nitriding on the surface of the metal core type skd61 series in die casting molds. In the die casting process is a process in which a process by melting molten aluminum metal at a pouring temperature of 720 0 C , then the liquid is taken with a ladle inserted into the sleeve cylinder and then pressed by the piston to fill the iron casting cavity so that it forms a casting object called a brake drum. The service life is only 80,000 shoots while the standard uses 160,000 shoots in the sub-section of the steel mold of the casting brake drum product. And to find out the low life time, the cause of the wear is sought, tests are carried out including: analysis of chemical composition, visual, microstructure and hardness